Assessment of cooling photovoltaic-wind hybrid power controller system for ac load application in tropical climate condition / \c Mohd Irwan bin Yusoff. - Mohd Irwan Yusoff (School of Electrical System, Universiti Malaysia Perlis, 2015)
The main goal of this research is to optimize the photovoltaic/wind hybrid power generation for AC load application.